A blast without power - cell death induced by the tuberculosis-necrotizing toxin fails to elicit adequate immune responses - Maueroeder, C.; Chaurio, R. A.; Dumych, T.; Podolska, M.; Lootsik, M. D.; Culemann, S.; Friedrich, Ralf P.; Bilyy, R.; Alexiou, Christoph; Schett, Georg; Berens, C.; Herrmann, Martin; et al. (Cell Death and Differentiation, 2016)
In this study, we deploy a doxycycline-dependent suicide switch integrated in a tumor challenge model. With this experimental setup, we characterized the immunological consequences of cells dying by four distinct cell death stimuli in vivo. We observed that apoptotic cell death induced by expression of the truncated form of BH3 interacting-domain death agonist (tBid) and a constitutively active form of caspase 3 (revC3), respectively, showed higher immunogenicity than cell death induced by expression of the tuberculosis-necrotizing toxin (TNT). Our data indicate that the early release of ATP induces the silent clearance of dying cells, whereas the simultaneous presence of 'find me' signals and danger-associated molecular patterns (DAMPs) promotes inflammatory reactions and increased immunogenicity. This proposed model is supported by findings showing that the production and release of high concentrations of IL-27 by bone-marrow-derived macrophages (BMDM) is limited to BMDM exposed to those forms of death that simultaneously released ATP and the DAMPs heat-shock protein 90 (HSP90) and high-mobility group box-1 protein (HMGB1). These results demonstrate that the tissue microenvironment generated by dying cells may determine the subsequent immune response.
EVALuna2:13264